Reforming Journalism - Olasky, Marvin N. (New Jersey : P&R Publishing Company, 2019)
"Marvin Olasky, editor-in-chief of World magazine, lays out the foundational principles, practical techniques, and history of journalism, showing us how to become citizen-reporters and discerning consumers of news"--
Two countries, one hope -- Why be a journalist? -- Biblical objectivity -- Directed reporting -- Street-level journalism and the ladder of abstraction -- Eyes, ears, noses -- Biblical sensationalism -- Sojourning in non-Christian lands -- Third brother journalism -- Interacting with atheists -- How to interview -- Writing profiles -- Organizational strategies -- The parts of a story -- Investigating Christian groups -- Investigating officials -- Good writing in English -- Using words accurately -- Character and personality of good journalists -- When readers complain -- The official story and the Protestant Reformation -- Revolution and counter-revolution -- A moderate revolution that lasts -- Developing and defending Christian journalism -- When societies break down -- Pro-life journalism, socialist journalism -- Slouching toward socialism and post-modernism -- Ideological battles -- The recent American journalistic tilt -- Current American reporting: Shemei journalism -- Factual accuracy and humble sowing
Includes bibliographical references (p. 353-358) and indexes.
Keywords: Protestant press -- History; Journalism, religious -- Methodology; Journalism, religious -- Philosophy